The usefulness of small-sided games on soccer training - Manuel Clemente, Filipe (2019)
The specificity of collective sports training has evolved to adapt according to ecology stimuli inherent to the sport. In this sense, the coaches have adopted exercises based on the game, designated by small-sided games. In football practice this type of exercises triggers very receptivity on the part of coaches. In this sense, this paper analyzes the relevance of this type of exercise and as may be appropriate depending on the specific needs of the players. Task constraints as field dimensions, number of players for exercises or objectives of the task showed effects on physiological and technical variables of the players. Consequently this article will examine through a literature review, the effects related to the task constraints in order to emphasize the massive relevance of smallsided soccer games.